EFEKTIVITAS DAN EFISIENSI FUNGSI KEUANGAN MELALUI AUDIT OPERASIONAL - Gaffar, Abdul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out whether the effecively and efficient financial function can be known with operational audit. The data has been collected by using: preliminary survey, internal control system test, and field research. The data source is primary and secondary data which have been analyzed by using descriptive qualitative approach with case study research method. With operational audit found the result of research shows that the assessment of PT âXâ is based on findings which refer to the weakness of financial function controlKeywords: financial function, operational audit, effective, efficient